(untitled) (Research, Society and Development, 2021)
Potassium bromate (KBrO3) is an oxidizing agent synthesized from bromine with potassium hydroxide, forming a salt with excellent technological and economic results when used in the production of bread, particularly of the French type, as it acts in strengthening the chain of gluten, being possible to incorporate a greater volume of air in the mass, thus improving the final result. However, since 2001, its use in Brazil has been banned, as it was discovered that this salt has a high carcinogenic and genotoxic potential. The analysis of potassium bromate is very important, as it provides information on the bromate residue present in the final product, due to its application in the bakery sector which, despite being illegal, can still be identified, given the advantage of its use in relation to substances legally used for the same purpose. Whether due to lack of inspection, lack of good manufacturing practice or due to soft laws. In this sense, this work aims to identify KBrO3 in French breads in the city of Belém, State of Pará, through experimental qualitative analysis using a direct method. Twenty (20) random samples from supermarkets and bakeries from different neighborhoods were analyzed, of which 17 (seventeen) showed a positive response for the presence of residual bromate. Therefore, it is evident that this additive is still part of the French-type bread production routine putting the consumer’s health at risk.